2006
DOI: 10.1111/j.0022-1112.2006.00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in potential and realized growth rates of age‐0 year northern rock sole

Abstract: The possibility of prey limitations on the growth performance of age‐0 year northern rock sole Lepidopsetta polyxystra was evaluated at three sites along the north‐east coast of Kodiak Island, Alaska, U.S.A., by comparison of observed to potential growth rates. Growth potential was measured in the laboratory across the range of temperatures encountered by this species during the first summer of life. Growth potential (gL, mm day−1) increased with water temperature (T) between 2 and 13° C, according to: gL = 0·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Furthermore, the Bering Sea populations of all 3 species increased in abundance during warming trends associated with the late-1970s regime shift (Bakkala 1993, Hare & Mantua 2000, Hoff 2006. Lastly, laboratory experiments have demonstrated that somatic growth of northern rock sole increases with temperature (Hurst & Abookire 2006), consistent with the relationships between climate and master chronologies noted in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the Bering Sea populations of all 3 species increased in abundance during warming trends associated with the late-1970s regime shift (Bakkala 1993, Hare & Mantua 2000, Hoff 2006. Lastly, laboratory experiments have demonstrated that somatic growth of northern rock sole increases with temperature (Hurst & Abookire 2006), consistent with the relationships between climate and master chronologies noted in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In a separate growth study, halibut grew 48% faster than rock sole at warm (10°C) temperatures whereas rock sole grew 16% faster than halibut at cold (2°C) temperatures (Hurst & Abookire 2006). These physiological differences most likely form the base mechanism by which DDHS varied between the species at warm and cold temperatures.…”
Section: Ontogeny and Temperature Effectsmentioning
confidence: 88%
“…Mean salinity and DO were greater at D simple than at the other sites in 2005 (Table 5), but differences were not Spatial variation in growth rates of fishes in both freshwater streams and tidal estuarine systems have been associated with site-specific food availability (e.g. Hurst & Abookire 2006, Arnekleiv et al 2006, density (e.g. Lobón-Cerviá 2005), and the presence of predators (e.g.…”
Section: Field Growth Ratesmentioning
confidence: 97%